A viabilidade econômica da instalação de energia solar em comunidades remotas do Amazonas - Pedrosa, Wendy Milla Brito (Brasil, 2024)
The research aimed to analyze the economic feasibility of installing solar energy in hard-to reach communities in the state of Amazonas, where the majority of the population is Indigenous and Quilombola, contributing to the reduction of social inequality in Brazil. The analysis considered the initial investment in photovoltaic equipment, state tariffs, investments in inverters, and energy storage systems. Despite the high initial installation cost, the long-term benefits include ease of installation, as solar energy does not depend on a conventional grid, job creation in system maintenance, improved quality of life with access to leisure and basic health care, and the use of household appliances. The cost analysis for households and communities showed that solar energy reduces dependence on fossil fuels, common in isolated municipalities, and contributes to environmental preservation by reducing greenhouse gas emissions. It is concluded that, despite the initial challenges, installing solar energy in isolated communities in Amazonas is economically viable and represents a crucial step towards the regional and sustainable development of one of the largest forests on the planet.